Pengaruh Work Life Balance, Organizational Commitment Terhadap Turnover Intention Melalui Job Satisfaction Kepada karyawan PT X - Luthfia Melati Fefinda Pulungan; Tiara Puspa (STMIK Widuri Jakarta, 2025)
This study aims to analyze the influence of Work Life Balance (WLB) and Organizational Commitment (OC) on Turnover Intention (TI) through Job Satisfaction (JS) among employees of PT. X, a multinational company in the logistics sector. The research is grounded in the view that job satisfaction plays a crucial role in shaping employees’ behavioral intentions and serves as a relevant mediator between WLB and employee behavior. A quantitative method was employed by distributing questionnaires to employees across various divisions using random sampling. The questionnaire consisted of personal information and items measuring WLB, OC, JS, and TI, all constructed in accordance with organizational research ethics. Data collection was conducted among employees working in different operational and administrative functions. The results indicate that both WLB and OC affect TI directly as well as indirectly through JS. Employees who are able to balance their work and personal life, and who demonstrate strong commitment to the company, tend to experience higher job satisfaction, which subsequently reduces their intention to leave. Conversely, poor work–life balance increases the risk of turnover, leading to substantial costs associated with employee loss. These findings align with previous literature suggesting that factors such as WLB and job satisfaction significantly influence employees’ decisions to remain in or leave an organization.